The Risorgimento in italian history, politics and memory during the national jubilees (1911-1961-2011) - Gori, Annarita (2015)
ln 2011, Italy celebrated its national jubilee. It was the third time that the country was called to confront its past, the complex process of nation-building and, as on the previous anniversaries, to deal with the issue famously highlighted by the liberal politician Massimo D'Azeglio: 'Italy is made; now the Italians must be made'. The meanings underlying these three celebrations allow us to reflect on the different ways in which the past history of the country was used by the ruling classes to build a sense of identity; and to underline how this process developed throughout the century. Jubilees are considered here not only as an anniversary, but also as a 'procedure employed by national state and by specific polity cultures to define themselves, and with the ways in which the politics of memory, legitimization strategies, languages of political communication and commemorative machineries have served as channel liable to persuade and to penetrate society' (Baioni, 2011: 399). These commemorations, in fact, were important occasions for reflection for polities and civil society, and for social scientists as well: in addition to being a celebratory moment, they were also significant events which encouraged reflection on Italian national identity and the relationship between polities, memory and the Risorgimento. The Risorgimento is a crucial period in Italian history: it marks the foundation of Italy as a united nation, but it is also the defining moment for some problematic divisions that have characterized the country: masses vs. elites; South vs. North; monarchy vs. republic, etc. For these reasons, the Risorgimento, its uses and its interpretations, will be the focus of this chapter: analysing the myth of the Risorgimento through the lens of the jubilees will help shed light on some basic problems of Italian history of the last 150 years, such as national identity in dispute between political parties and local belonging, historical revisionism, the persistence of divisions and the relationship with the national anniversaries of other countries.